2016
DOI: 10.1104/pp.15.01906
|View full text |Cite
|
Sign up to set email alerts
|

WRINKLED1 Rescues Feedback Inhibition of Fatty Acid Synthesis in Hydroxylase-Expressing Seeds

Abstract: Previous attempts at engineering Arabidopsis (Arabidopsis thaliana) to produce seed oils containing hydroxy fatty acids (HFA) have resulted in low yields of HFA compared with the native castor (Ricinus communis) plant and caused undesirable effects, including reduced total oil content. Recent studies have led to an understanding of problems involved in the accumulation of HFA in oils of transgenic plants, which include metabolic bottlenecks and a decrease in the rate of fatty acid synthesis. Focusing on engine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
58
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 63 publications
(61 citation statements)
references
References 63 publications
1
58
0
Order By: Relevance
“…Over-expression of ZmWRI1 increases the fatty acid content of the mature maize grain, the contents of certain amino acids, several compounds involved in amino acid biosynthesis, and two intermediates of the tricarboxylic acid cycle (Pouvreau et al, 2011). Similar attempts were also carried out in A. thaliana and resulted in a 10–40% increase in seed oil content, and increased seed size and mass (Adhikari et al, 2016; Kanai et al, 2016). Although WRI1 is the best understood example of the transcription factors that have been identified in A. thaliana seeds, only a few have been characterized in other plants and organs/tissues (Shen et al, 2010; Pouvreau et al, 2011; Dussert et al, 2013; Ma et al, 2013) and the role of WRI1 has never been reported in palm endosperm.…”
Section: Introductionmentioning
confidence: 60%
“…Over-expression of ZmWRI1 increases the fatty acid content of the mature maize grain, the contents of certain amino acids, several compounds involved in amino acid biosynthesis, and two intermediates of the tricarboxylic acid cycle (Pouvreau et al, 2011). Similar attempts were also carried out in A. thaliana and resulted in a 10–40% increase in seed oil content, and increased seed size and mass (Adhikari et al, 2016; Kanai et al, 2016). Although WRI1 is the best understood example of the transcription factors that have been identified in A. thaliana seeds, only a few have been characterized in other plants and organs/tissues (Shen et al, 2010; Pouvreau et al, 2011; Dussert et al, 2013; Ma et al, 2013) and the role of WRI1 has never been reported in palm endosperm.…”
Section: Introductionmentioning
confidence: 60%
“…Previous studies indicated that WRI1 acts as the master regulator of FA biosynthesis by directly promoting the expression of SUS2, PI-PKb1, BCCP1, BCCP2, KASI, GLB1, and ROD1 and indirectly inducing ACP1, CAC2, CAC3, BIO2, PDH E1a, KASIII, MOD1, and LAS during Arabidopsis seed development (Focks and Benning, 1998;Cernac and Benning, 2004;Masaki et al, 2005;Baud et al, 2007;Maeo et al, 2009;To et al, 2012). ROD1 also was demonstrated to be up-regulated by overexpressing Arabidopsis WRI1 in N. benthamiana leaves (Grimberg et al, 2015) and castor (Ricinus communis) seeds (Adhikari et al, 2016). Thus, alterations in the FA profile of myb89 seeds become complicated and cannot be attributed to specific genes.…”
Section: Discussionmentioning
confidence: 94%
“…WRI1, which is the TF of the APETALA2-ethylene-responsive element-binding protein family, directly or indirectly targets some enzymes involved in the late glycolysis and plastidial fatty acid (FA) biosynthetic network (Cernac and Benning, 2004;Baud et al, 2007;Maeo et al, 2009). Mutations in wri1 cause an 80% reduction in Arabidopsis seed oil content (Focks and Benning, 1998), and overexpression of WRI1 leads to a significant increase in the oil content (Cernac and Benning, 2004;Maeo et al, 2009;Sanjaya et al, 2011;Grimberg et al, 2015;Adhikari et al, 2016). LEC1 encodes a protein that is homologous to the Saccharomyces cerevisiae HEME ACTIVATOR PROTEIN3 or mammalian NUCLEAR FACTOR YB subunit of the heterotrimeric CCAAT boxbinding factor (Lotan et al, 1998;Lee et al, 2003).…”
mentioning
confidence: 99%
“…The seed oil content of HFA producing lines can be at least partially recovered by upregulating acetyl-CoA carboxylase (Adhikari, Bates, & Browse, 2016) or by coexpression of the hydroxylase with HFA selective TAG synthesis enzymes (RcDGAT2 or (van Erp et al, 2011;Bates et al, 2014;van Erp et al, 2015)). The more efficient incorporation of HFA into TAG by HFA selective DGAT or PDAT apparently reduces the negative effect of HFA on lipid metabolism indicated by a recovered in vivo acetyl-CoA carboxylase activity and more seed oil (Bates et al, 2014).…”
Section: Brassica Napus (Canola/rapeseed) and The Emerging Biotech Cropmentioning
confidence: 99%
“…For example, variations in HFA content and oil quantity in the same genetic lines have been reported between different sets of experiments performed over a 10-year span (Adhikari et al, 2016;Bates et al, 2014;Bayon, Chen, Weselake, & Browse, 2015;Burgal et al, 2008;Lu et al, 2006;Lunn et al, 2018;van Erp et al, 2011van Erp et al, , 2015.…”
Section: Rcpdat1mentioning
confidence: 99%